Importance of Proprioceptive Information for Postural Control in Children with Strabismus before and after Strabismus Surgery - Bucci, Maria P.; Soufi, Hayette; Villeneuve, Philippe; Colleville, Lucile; Bui-Quoc, Emmanuel; Lions, Cynthia (Frontiers in Systems Neuroscience, 2016)
The objective of this study is to examine the role of proprioception in postural balance in children with strabismus before and after realignment of their visual axes by eye surgery. Postural recordings were made with the TechnoConcept® force platform in twenty three children. Several conditions were studied, whether the subjects had both eyes open, or either the dominant or the non-dominant eye open, without and with foam pads of 4 mm underfoot. Recordings were performed before and after strabismus surgery. The surface area, the length and the mean speed of the center of pressure (CoP) were analyzed. Before strabismus surgery, all children showed better stability with both eyes open with respect to the condition with the non dominant eye open; furthermore postural stability improved in the presence of foam pads. After surgery, all postural parameters (surface area, length and mean speed of CoP) decreased significantly, especially in the non-dominant eye viewing condition. We suggest that strabismic children use mainly proprioceptive information in order to control their posture, but also visual inputs, which are important for obtaining a good postural stability. The alignment of the visual axes after surgery provides enhanced postural stability, suggesting, again the major role of visual inputs in the control of posture. Proprioceptive plasticity after strabismus surgery may allow better visual rehabilitation.